Association Between Macrophage Migration Inhibitory Factor -173 G>C Gene Polymorphism and Childhood Idiopathic Nephrotic Syndrome: A Meta-Analysis - Ying, Daojing; Jiang, Mengjie; Rong, Liping; Zhuang, Hongjie; Chen, Lizhi; Xu, Yuanyuan; Jiang, Xiaoyun (Frontiers in Pediatrics, 2021)
Background: Studies have identified that MIF -137 G>C gene polymorphism is associated with idiopathic nephrotic syndrome (INS) susceptibility and steroid resistance, but the results remain inconclusive. Methods: We searched PubMed, Embase, and Web of Science for relevant studies published before 31 March 2021. Pooled data were reported as odds ratio (OR) with 95% confidence interval (CI). Noteworthiness of significant OR was estimated by the false positive report probability (FPRP) test. Trial sequential analysis (TSA) was used to control type I and type II errors. Results: We selected seven case-control studies that included 1026 INS children (362 were steroid-resistant NS and 564 were steroid-sensitive NS) and 870 controls. The results showed that MIF -173 G>C polymorphism was significantly associated with INS susceptibility in allelic, heterozygous and dominant genetic models (C vs. G: OR = 1.325, 95% CI: 1.011-1.738; GC vs. GG: OR = 1.540, 95% CI: 1.249-1.899; CC + GC vs. GG: OR = 1.507, 95% CI: 1.231-1.845), and FPRP test and TSA indicated that the associations were true in heterozygous and dominant models. The pooled results also revealed that MIF -173 G>C polymorphism was significantly associated with steroid resistance in allelic, homozygous and recessive models (C vs. G: OR = 1.707, 95% CI: 1.013-2.876; CC vs. GG: OR = 4.789, 95% CI: 2.109-10.877; CC vs. GC + GG: OR = 4.188, 95% CI: 1.831-9.578), but FPRP test indicated that all these associations were not noteworthy. Furthermore, TSA revealed that the non-significant associations between MIF -173 G>C polymorphism and steroid resistance in heterozygous and dominant models were potential false negative. Conclusions: This meta-analysis could draw a firm conclusion that MIF -173 G>C polymorphism was significantly associated with increased INS risk in heterozygous and dominant genetic models. MIF -173 G>C polymorphism was not likely to affect steroid responsiveness, but more studies were needed to confirm.